Geomorphic influences on the distribution and accumulation of pyrogenic carbon (PyC) following a low severity wildfire in northern New Mexico. Issue 10 (23rd May 2018) - Galanter, Amy; Cadol, Daniel; Lohse, Kathleen
Abstract: The distribution, transport, and accumulation of wildfire‐generated pyrogenic carbon (PyC) has important consequences for contaminant transport and carbon cycling, but a conceptual model for PyC accumulation and loss that includes geomorphic processes is lacking. In this study we quantified PyC concentration in soil samples collected from the Jemez Mountains of New Mexico before and after the 2013 Thompson Ridge (TR) fire, and developed a conceptual model describing PyC redistribution. Pre‐fire samples were fortuitously collected 4 years before the TR burn and post‐fire samples were collected at the same locations 15 months following the TR fire. Samples were collected from the O and A horizon, with sites representing a range of slope angle, aspect, burn severity, and geomorphic setting. PyC was determined by a modified chemo‐thermal oxidation method to compare PyC to total organic carbon (TOC). The mean PyC/TOC ratio was significantly higher post‐fire than pre‐fire (0.14 vs 0.12), indicating increased PyC sequestration. O horizon PyC concentrations were more variable and more responsive to fire than the A horizon. Soil horizon, watershed, and geomorphic setting proved to be the most influential factors in predicting PyC concentration changes. PyC concentrations increased most on hillslopes and in low‐severity burn areas, suggesting higher rates of PyC production or post‐fire accumulation. Burn patchiness appears to facilitate PyC accumulation, with lower severity patches trapping PyC mobilized from high severity patches. While PyC content had greater point scale variance following the fire, the fire also homogenized pre‐fire PyC differences between soil horizons and among watersheds within the burn perimeter, differences that appear to develop over time between fires. The O horizon is a larger sink for PyC in the short term following fire, but based on pre‐fire concentrations the A horizon appears to be a more stable sink for PyC. Copyright © 2018 John Wiley & Sons, Ltd. Abstract : Pre‐ and post‐fire samples of soil pyrogenic carbon (PyC) show that this recalcitrant component of the carbon cycle becomes more abundant but also more spatially heterogeneous following a fire and subsequent geomorphic redistribution. Fire also had the effect of homogenizing pre‐fire PyC differences between soil horizons and among neighboring watersheds, differences that appear to develop over time between fires. Burn patchiness appears to facilitate PyC accumulation, with lower severity patches trapping PyC mobilized from high severity patch.